NGHIÊN CỨU CHẾ TẠO ỐNG VI CHIẾT PHA RẮN MAO QUẢN HỞ - Đoàn, Đặng Văn; Huy, Đỗ Quang; Huệ, Nguyễn Đức; Trí, Trần Mạnh (Vietnam Journal of Science and Technology, 2012)
STUDY ON MAKING WALL COATED OPEN TUBULAR FOR- SOLID PHASE MICROEXTRACTION Wall Coated Open Tubular - Solid Phase Microextraction (WCOT-SPME) is sample preparing method in chromatographic analysis which was improved on solid phase microextraction (SPME). This method is based on the sorption balance of compounds from sample onto a stationary phase thin film, which coated on inner surface of needle. In this subject, we studied to make the WCOT-SPME divice on five stationary phases. After that, calculating the thickness of film coater and comparing with the observation results by Scanning Electron Microscope (SEM) method.